Medieval political thought St. Augustine and St. Thomas Aquinas - Casambre, Athena Lydia Cera 1946- (Quezon City U.P. Diliman Interactive Learning Center, 2006)
The second phase in the lecture series for Social Science II, addressing the topics on medieval political thought, political obligation and legitimacy, liberal political economy, rise of positivism, and root of social constructivism.
Lecture delivered on July 5, 2006.
Co-produced by, Office of the Vice-President for Academic Affairs ; U.P. Open University Media Center ; U.P. Computer Center ; Department of Electrical and Electronics Engineering, College of Engineering ; Department of Political Science, College of Social Sciences and Philosophy.
Series Lecturer: Athena Lydia Casambre ; Moderator: Malaya C. Ronas.
Keywords: Augustine -- Saint, Bishop of Hippo -- Congresses. -- Philosophy; Thomas, Aquinas -- Saint -- 1225n-1274 -- Congresses. -- Philosophy; Philosophy, Medieval -- Congresses